An Automated Homogeneous Immunoassay for Quantitating Imatinib Concentrations in Plasma. Issue 4 (August 2015) - Beumer, Jan H.; Kozo, Daniel; Harney, Rebecca L.; Baldasano, Caitlin N.; Jarrah, Justin; Christner, Susan M.; Parise, Robert; Baburina, Irina; Courtney, Jodi B.; Salamone, Salvatore J.
Abstract : Background: Imatinib pharmacokinetic variability and the relationship of trough concentrations with clinical outcomes have been extensively reported. Although physical methods to quantitate imatinib exist, they are not widely available for routine use. An automated homogenous immunoassay for imatinib has been developed, facilitating routine imatinib testing. Methods: Imatinib-selective monoclonal antibodies, without substantial cross-reactivity to the N -desmethyl metabolite or N -desmethyl conjugates, were produced. The antibodies were conjugated to 200 nm particles to develop immunoassay reagents on the Beckman Coulter AU480 analyzer. These reagents were analytically validated using Clinical Laboratory Standards Institute protocols. Method comparison to liquid chromatography tandem mass spectrometry (LC-MS/MS) was conducted using 77 plasma samples collected from subjects receiving imatinib. Results: The assay requires 4 µL of sample without pretreatment. The nonlinear calibration curve ranges from 0 to 3000 ng/mL. With automated sample dilution, concentrations of up to 9000 ng/mL can be quantitated. The AU480 produces the first result in 10 minutes and up to 400 tests per hour. Repeatability ranged from 2.0% to 6.0% coefficient of variation, and within-laboratory reproducibility ranged from 2.9% to 7.4% coefficient of variation. Standard curve stability was 2 weeks and on-board reagent stability was 6 weeks. For clinical samples with imatinib concentrations from 438 to 2691 ng/mL, method comparison with LC-MS/MS gave a slope of 0.995 with a y -intercept of 24.3 and a correlation coefficient of 0.978. Conclusions: The immunoassay is suitable for quantitating imatinib in human plasma, demonstrating good correlation with a physical method. Testing for optimal imatinib exposure can now be performed on routine clinical analyzers.